2021
DOI: 10.21608/eajbsf.2021.223216
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological and Biological Studies on Using Lufenuron, Chlorpyrifos, Spinosad and Emamectin Benzoate Insecticides for Controlling Cotton Leafworm, Spodoptera littoralis (Boisd.)

Abstract: http://eajbsf.journals.ekb.eg/ Toxicological and Biological Studies on Using Lufenuron, Chlorpyrifos, Spinosad and Emamectin Benzoate Insecticides for Controlling Cotton Leafworm, Spodoptera littoralis (Boisd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…The main categories of IGRs are Juvenile hormone (JH) mimics and chitin synthesis inhibitors (CSIs) (Tunaz and Uygun, 2004). Several studies have investigated the efficacy of IGRs against S. littoralis (El-Sheikh & Aamir, 2011;Elsayed et al, 2017 andAbdel Aziz &El-Gabaly, 2021) evaluated the efficacy of lufenuron against S. littoralis. Similarly, Mageed et al (2018) investigated the effectiveness of chlorfluazuron against S. littoralis and reported that the mortality and sublethal effects of chlorfluazuron in insects, can provide a truly selective insecticide.…”
Section: Introductionmentioning
confidence: 99%
“…The main categories of IGRs are Juvenile hormone (JH) mimics and chitin synthesis inhibitors (CSIs) (Tunaz and Uygun, 2004). Several studies have investigated the efficacy of IGRs against S. littoralis (El-Sheikh & Aamir, 2011;Elsayed et al, 2017 andAbdel Aziz &El-Gabaly, 2021) evaluated the efficacy of lufenuron against S. littoralis. Similarly, Mageed et al (2018) investigated the effectiveness of chlorfluazuron against S. littoralis and reported that the mortality and sublethal effects of chlorfluazuron in insects, can provide a truly selective insecticide.…”
Section: Introductionmentioning
confidence: 99%